2017
DOI: 10.1158/1078-0432.ccr-17-0257
|View full text |Cite
|
Sign up to set email alerts
|

Analytic, Preanalytic, and Clinical Validation of p53 IHC for Detection of TP53 Missense Mutation in Prostate Cancer

Abstract: PURPOSE TP53 missense mutations may help to identify prostate cancer (PCa) with lethal potential. Here, we pre-analytically, analytically and clinically validated a robust immunohistochemistry (IHC) assay to detect subclonal and focal TP53 missense mutations in PCa. EXPERIMENTAL DESIGN The p53 IHC assay was performed in a CLIA-accredited laboratory on the Ventana Benchmark immunostaining system. p53 protein nuclear accumulation was defined as any p53 nuclear labeling in >10% of tumor cells. 54 formalin fixed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 50 publications
5
62
0
Order By: Relevance
“…These findings show that even older antibodies can be re-examined using more modern technologies to validate their assay properties. Also, as is the case for PTEN, the p53 IHC assay was robust to pre-analytic fixation conditions and could be useful in identifying heterogeneous, subclonal TP53 alterations in the setting of prostate biopsies that may be difficult to detect without next generation sequencing approaches [89] . The ability to interrogate p53 status by a simple IHC assay in primary and metastatic prostate tumors could be highly useful for studies of disease pathogenesis and for developing predictive biomarkers.…”
Section: Examples Of Ihc Assays and Insights They Have Facilitatedmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings show that even older antibodies can be re-examined using more modern technologies to validate their assay properties. Also, as is the case for PTEN, the p53 IHC assay was robust to pre-analytic fixation conditions and could be useful in identifying heterogeneous, subclonal TP53 alterations in the setting of prostate biopsies that may be difficult to detect without next generation sequencing approaches [89] . The ability to interrogate p53 status by a simple IHC assay in primary and metastatic prostate tumors could be highly useful for studies of disease pathogenesis and for developing predictive biomarkers.…”
Section: Examples Of Ihc Assays and Insights They Have Facilitatedmentioning
confidence: 99%
“…Moreover, studies in prostate cancer showed that overexpression of p53 in tumor cells was predictive of poor outcome [88] , but there were very few studies analyzing in detail with automated clinical grade IHC assays whether positive IHC staining for p53 in prostate carcinoma correlated with TP53 mutation. Recently, using a series of cell lines with known TP53 status we worked up a previously existing IHC antibody that was being used in a clinical laboratory and found that it was highly specific for TP53 missense mutations in prostate cancer [89] . Using this assay on human prostate samples we reported that p53 overexpression was approximately 85% sensitive for detecting a TP53 missense mutation.…”
Section: Examples Of Ihc Assays and Insights They Have Facilitatedmentioning
confidence: 99%
“…Briefly, PTEN immunohistochemistry was performed in a Clinical Laboratory Improvement Amendments (CLIA)‐accredited laboratory by use of a genetically validated protocol developed by our group for the Ventana autostaining system (Ventana/Roche Medical Systems, Tucson, AZ, USA), with a rabbit monoclonal antibody (D4.3; Cell Signaling Technologies, Danvers, MA, USA). p53 immunohistochemistry was performed in a CLIA‐accredited laboratory by use of a genetically validated protocol developed by our group, with a mouse monoclonal antibody (BP53‐11; Ventana/Roche Medical Systems). Scoring for both assays was performed with a dichotomous system as previously described …”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of staining intensity is based on the data suggesting that a high degree of p53 expression significantly correlates with the gene mutation, while a weak reaction can be associated with a physiological accumulation of the protein in the conditions of cellular stress or disturbance of some regulatory interactions [11]. The 10% cutoff was often used for the evaluation of positive expression in the studies of PC [8,12,13]. A lower fraction of positive nuclei (<10%) correlated stronger with the presence of a wild gene in the analysis of ovarian carcinoma [11].…”
Section: Materials and Methods The Study Population Included 119 Patmentioning
confidence: 99%